Textbook Evaluation Criteria and Learning Achievement in Secondary Schools in Kenya and Japan: Addressing Instructional Content and Pedagogy - Sarah Getahun Bekele; Paul Odundo Amolo; Ganira Khavugwi Lilian (Newinera Publisher, 2022)
Knowledge and skills are enhanced if instructional content support lively learning experiences for increased learner achievement. Study presents literature review of related literature on textbook evaluation criteria in secondary education in Kenya and Japan. Assessing quality of instructional content has enhanced effective teaching and learning in secondary schools in Kenya promoting self-efficacy among learners. However in instances where techniques of presenting instructional content do not accommodate learner centered approach learning outcome is propelled resulting in success in learning. Research question for this study is focused on relationship between evaluation criteria in Kenya and Japanese system of education. The study dimensions include teaching methods and instructional content. The purpose of this desk review is to establish suitability of evaluation criteria in promoting learning achievement in Kenya and Japanese system of education. Design adopted for this study is systematic literature review in the area of pedagogy, instructional content and evaluation Criteria. The articles reviewed are those published in the last five years from global view point and African perspective. The study concluded that both Kenya and Japan offer business studies at secondary level and that both of the countries encourage learner centered pedagogical technique to enhance academic outcome. The study recommends that Kenya improves on content presentation to integrate digital textbooks to enhance online learning for lifelong learning experience.